The Effect of Isometric Exercises on Primary Dysmenorrhea: A Randomized Controlled Clinical Trial - Azima, Sara; Rajaei Bakhshayesh, Hajar; Abbasnia, Keramatollah; Kaviani, Maasumeh; Sayadi, Mehrab (Galen Medical Journal, 2023)
Background: Primary dysmenorrhea is the most common cyclic pelvic pain and is also the most common gynecological problem worldwide and affects quality of life. The present study aimed to investigate the effect of isometric exercises on intensity and duration of pain and level of anxiety in the students with primary dysmenorrhea. Materials and Methods: In this randomized controlled clinical trial, 68 students living in dormitories of Shiraz University with primary dysmenorrhea Â were randomly assigned to isometric exercises and control groups. The intervention group performed isometric exercises since the third day of the menstrual cycle for 8 weeks. Pain intensity was measured using Visual Analog Scale (VAS). In addition, the anxiety level was assessed using Spielberger questionnaire. The data were analyzed using independent t-test, repeated measures ANOVA, and Bonferroni Post hoc test at the end of the second and third months of the study. Besides, P<0.05 was considered as statistically significant. Results: Pain intensity and duration of pain was significantly reduced in exercises group (p<0.001). However, no significant difference was found between the two groups concerning the mean anxiety levels. Conclusion: Primary dysmenorrhea is a common complaint among young women. Isometric exercises seem to be an easy, non-pharmacological method for reducing primary dysmenorrheal.